Producción de soya (Glycine max (L.) Merril) y frijol (Phaseolus vulgaris (L.) comparada con el método de parcelas - Carmen C., Horacio; Bastidas R., Gilberto (Instituto Colombiano Agropecuario, 2019)
The hills method can be useful to maximize the research resources because it requires less space, less plant and less time in preliminary evaluations of yield compared with plots. The objective of the study was to see the correlation between plots and hills methods in soybean and dry beans. The experiment was carried out for two semesters (1984B and 1985A) in Palmira, Colombia, located at 1006 m.a.s.l., with a mean temperature of 24°C. The following variables were taken at harvest time: Yield (kg/ha), pods number, nodes number, branches number and plant height. The experiment included 16 lines of dry beans and 25 of soybean. A randomized complete block design was used with four replications. It was found significant correlations at the 1% level in two semesters of evaluation in five variables to soybean. The figures of 0.7328, 0.6749, 0.8625, 0.8831 and 0.684, were observed for yield, pod number, nodes number, branches number, height plant, respectively. In dry beans only was found correlation significant at the 5% level for yield in the 1 985A semester, and correlation significant for nodes number in the two semesters. The C.V. was found greater in hills than plots for both especies; there fore more site in hill method would be desirable.